2021
DOI: 10.5812/compreped.116104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of High-Flow Nasal Oxygen on Respiratory Parameters and Pulmonary Complications After Early Extubation Following Pediatric Heart Surgery

Abstract: Objectives: The aim of this study was to evaluate the effect of high-flow nasal cannula (HFNC) after early extubation on children undergoing cardiac surgery. Methods: This randomized controlled clinical trial was performed among 92 children aged 1 to 24 months undergoing cardiac surgery from March 5 to August 30, 2020, in a pediatric post-cardiac surgery intensive care unit (ICU). The patients were randomized to receive either HFNC or conventional oxygen therapy after extubation. Arterial blood samples were co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 28 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…First, we conducted a sensitivity analysis to compare tracheal extubation failure rates between HFNC and COT groups. By excluding the study by Enayati et al, we found no substantial difference between HFNC and COT, and the heterogeneity was resolved (RR = 1.14, 95% CI: 0.52 to 2.49, p = .75, I 2 = 0%) 27 . Next, concerning postoperative LOS in HFNC versus NIV, despite performing sensitivity analyses, the heterogeneity remained unresolved.…”
Section: Resultsmentioning
confidence: 69%
See 3 more Smart Citations
“…First, we conducted a sensitivity analysis to compare tracheal extubation failure rates between HFNC and COT groups. By excluding the study by Enayati et al, we found no substantial difference between HFNC and COT, and the heterogeneity was resolved (RR = 1.14, 95% CI: 0.52 to 2.49, p = .75, I 2 = 0%) 27 . Next, concerning postoperative LOS in HFNC versus NIV, despite performing sensitivity analyses, the heterogeneity remained unresolved.…”
Section: Resultsmentioning
confidence: 69%
“…Among these, 12 met the inclusion criteria. Of those, seven studies compared HFNC to NIV, 1,[20][21][22][23][24][25] four studies compared HFNC to COT, [26][27][28][29] and one was an observational single-arm study. 30 The studies comparing HFNC to NIV consisted of five observational cohort studies (one prospective and four retrospective), 1,20,22,24,25 one RCT, 21 and one case-controlled observational study.…”
Section: Literature Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Initial search retrieved 167 abstracts, of which 10 full texts were further assessed and six studies included. 12,13,[18][19][20][21] (Figure 1).…”
Section: Search Resultsmentioning
confidence: 99%